Clinical and morphological predictors of metastasis in papillary thyroid microcarcinoma - Varlamov, Andrey; Elfimova, Alina; Matrosova, Alina; Pachuashvili, Nano; Dzodzaeva, Ariya; Slashchuk, Konstantin; Nikiforovich, Petr; Beltsevich, Dmitry; Vanushko, Vladimir; Urusova, Liliya (Frontiers in Endocrinology, 2025)
IntroductionPapillary thyroid microcarcinomas (PTMCs), defined as papillary thyroid carcinomas measuring ≤1 cm, are frequently diagnosed incidentally and are generally associated with favorable outcomes. However, a significant subset of patients develops regional lymph node metastases. This study aimed to identify clinical and morphological features associated with metastatic spread in PTMCs. MethodsA total of 100 cases were retrospectively analyzed, including 50 with confirmed lymph node metastases and 50 without. A detailed histological assessment included evaluation of tumor subtype, nuclear features, presence of psammoma bodies, tumor “buds,” fibrosis, and other parameters. Clinical variables such as age, sex, body mass index, and presence of the BRAF V600E mutation were also considered. ResultsLogistic regression revealed that younger age, classical histological subtype, tumor “budding,” and presence of psammoma bodies were independently associated with an increased risk of regional metastases, while concomitant multinodular hyperplasia was negatively associated. DiscussionThe combination of these features may enhance risk stratification and guide the clinical management of PTMC patients, including decisions on surgical extent and follow-up strategies. Our findings support the relevance of comprehensive histological and clinical evaluation in predicting the metastatic potential of PTMCs.